A Front Tracking Method for the Simulation of Compressible Multimedium Flows (Communications in Computational Physics, 2018)
A front tracking method combined with the real ghost fluid method (RGFM)is proposed for simulations of fluid interfaces in two-dimensional compressible flows.In this paper the Riemann problem is constructed along the normal direction of interfaceand the corresponding Riemann solutions are used to track fluid interfaces. Theinterface boundary conditions are defined by the RGFM, and the fluid interfaces areexplicitly tracked by several connected marker points. The Riemann solutions are alsoused directly to update the flow states on both sides of the interface in the RGFM.In order to validate the accuracy and capacity of the new method, extensive numericaltests including the bubble advection, the Sod tube, the shock-bubble interaction,the Richtmyer-Meshkov instability and the gas-water interface, are simulated by usingthe Euler equations. The computational results are also compared with earlier computationalstudies and it shows good agreements including the compressible gas-watersystem with large density differences.